Cold Sintered LiMn2O4 for High-Rate Capability Electrodes. Issue 2 (1st February 2022) - Nur, Khushnuda; Roitzheim, Christoph; Finsterbusch, Martin; Bram, Martin; Guillon, Olivier
Abstract : This study provides for the first time a detailed investigation of the cold sintering of LiMn2 O4 (LMO). Aqueous based cold sintering aid facilitated densification of LMO at lower temperature range of 400 °C to 600 °C within a dwell time of merely 1 min to the relative density of 70%–80%, without any non—stoichiometry or the need of post annealing in air atmosphere. Connected porosity was observed in the cold sintered structure as confirmed by Mercury porosimetry and scanning electron microscopy analysis. Cold sintered and dry milled LMO delivered a specific discharge capacity of 121 mAh g −1 for the first discharge cycle at 0.1 C with an appreciably low capacity drop to 107 mAh g −1 at 15 C. In contrast, LMO powder, without any cold sintering treatment, provided merely 84 mAh g −1 at 0.1 C as initial discharge capacity and only 6 mAh g −1 at 2 C. This difference was interpreted as the removal/thinning of insulating Li2 CO3 layer from the LMO particles after being cold sintered as confirmed by X-ray diffraction, thermal analysis and Raman spectroscopy.